2021
DOI: 10.1001/jamanetworkopen.2021.13891
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Sequential Organ Failure Assessment Score for In-Hospital Mortality by Race and Relevance to Crisis Standards of Care

Abstract: IMPORTANCE Crisis Standards of Care (CSC) are guidelines for rationing health care resources during public health emergencies. The CSC adopted by US states ration intensive care unit (ICU) admission using the Sequential Organ Failure Assessment (SOFA) score, which is used to compare expected in-hospital mortality among eligible patients. However, it is unknown if Black and White patients with equivalent SOFA scores have equivalent in-hospital mortality.OBJECTIVE To investigate whether reliance on SOFA is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 45 publications
0
48
1
Order By: Relevance
“…where only the top priority tier would receive treatment, 15.6% of black patients were misclassified from the highest to the second priority. 4 Second, White and Lo claim that our conclusions are at best limited, due to a perceived erroneous description of their model. For example: 'Although it is plausible-but uncertainthat using the two-criterion framework they inaccurately described as the NJ framework may worsen disparities the actual four-criterion framework we developed is unlikely to worsen disparities and would probably mitigate them'.…”
Section: Responsementioning
confidence: 84%
See 1 more Smart Citation
“…where only the top priority tier would receive treatment, 15.6% of black patients were misclassified from the highest to the second priority. 4 Second, White and Lo claim that our conclusions are at best limited, due to a perceived erroneous description of their model. For example: 'Although it is plausible-but uncertainthat using the two-criterion framework they inaccurately described as the NJ framework may worsen disparities the actual four-criterion framework we developed is unlikely to worsen disparities and would probably mitigate them'.…”
Section: Responsementioning
confidence: 84%
“…We, therefore accurately characterised the multiprinciple strategy and its consequences, and more robust (including broadly concurrent) data than presented by White and Lo show that the Model Guidance as integrated into the NJ Directive indeed exacerbates black patients' disadvantage. [3][4][5] In a broader perspective, this situation raises critical questions about the obligations of authors of high-stake guidelines to inform users about important updates in an accurate, transparent and timely manner as well as regarding other structures that avoid triage decisions being based on outdated frameworks.…”
Section: Responsementioning
confidence: 99%
“…16 Another large retrospective study of ICU patients admitted prior to the COVID-19 pandemic also found that the SOFA score overestimated mortality among Black patients. 18 Another study that looked at 3 priority groupings of critically ill patients in 2 hospitals in Florida during the pandemic found no difference in priority groupings between patients in different racial categories. 7 The Massachusetts Department of Public Health published guidelines for the allocation of scarce resources on April 7, 2020, using the SOFA score as a proxy for likelihood of acute survival and a comorbidities score as a proxy for likelihood of long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…Crisis Standards of Care and Estimated Excess Mortality by Race and Ethnicity During COVID-19 length of stay of 13(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) days. A total of 119 patients (23.9%) died during the hospitalization, and 165 (45.3%) were discharged home without hospice.…”
mentioning
confidence: 99%
See 1 more Smart Citation